2020
DOI: 10.1101/2020.07.17.207019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of SARS-CoV-2 3CL Protease Inhibitors by a Quantitative High-throughput Screening

Abstract: Background and PurposeThe COVID-19 caused by SARS-CoV-2 has emphasized the urgent need for therapeutic development. Drug repurposing screening is the most practical and rapid approach for discovery of such therapeutics. The 3CLpro, or main protease (Mpro) of SARS-CoV-2 is a valid drug target as it is a viral enzyme with an essential role in viral replication, and cleavage specificity that is distinct from host proteases.Experimental ApproachWe employed and miniaturized a fluorogenic 3CLpro enzyme assay in whic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
(51 reference statements)
0
10
0
1
Order By: Relevance
“…This cleavage is mediated by two virally encoded proteases: the main viral protease, known as Mpro, 3CLpro or non-structural protein 5 (nsp5) and a second protease known as the papain-like protease, PLpro, a domain within nsp3 3 . There is much interest in developing de-novo inhibitors to target these proteases [5][6][7][8][9][10] but the full clinical development of such drugs is a time-consuming process, usually requiring several years.…”
Section: Introductionmentioning
confidence: 99%
“…This cleavage is mediated by two virally encoded proteases: the main viral protease, known as Mpro, 3CLpro or non-structural protein 5 (nsp5) and a second protease known as the papain-like protease, PLpro, a domain within nsp3 3 . There is much interest in developing de-novo inhibitors to target these proteases [5][6][7][8][9][10] but the full clinical development of such drugs is a time-consuming process, usually requiring several years.…”
Section: Introductionmentioning
confidence: 99%
“…While multiple assays exist to evaluate protease inhibitors, an assay of the nature we envisioned has clear advantages, as it requires minimal upfront cost or effort, is accessible to many biomedical research labs, does not involve the use of live virus, and requires no specialized reporter to read out protease activity. In contrast, in vitro protease assays using purified protein have formed the backbone of inhibitor screening, but require upfront efforts to isolate the pure protease and are not conducted under physiologic cellular conditions 13,14 . In addition, if one desires to identify broad-acting coronavirus inhibitors, one must purify and identify experimental conditions suitable for testing each protease in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our studies identified the potential to target SARS-CoV-2 nucleocapsid with suramin analogs and proposed analogs possessing enhanced affinity and specificity. This approach could also be applied to the 3CL protease which was recently identified as another possible suramin binding target (40). Our phylogenetic and evolutionary analyses also suggest that the suramin binding pockets are evolutionary conserved in related coronavirus RdRp and nucleocapsid proteins which could make these suramin analogs more broadly applicable therapeutics against this group of viral pathogens.…”
Section: Discussionmentioning
confidence: 70%